HUMAN RESOURCES MANAGEMENT IN AN ISLAMIC PERSPECTIVE: A REVIEW OF THE QUR'AN - Samsul Aripin Pahruroji; Mulyawan Safwandy Nugraha (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to determine Human Resource Management in an Islamic Perspective: Review of the Qur'an using descriptive qualitative research methods, quoting several verses of the Qur'an related to Human Resource Management. Human resource management is deemed necessary for the development of an organization and for managing all employee activities. Employees are expected to be able to realize the goals to be achieved in an organization. Human resource management includes determining employee activities starting from employee selection, training and development as well as all activities related to employee activities within the scope of the organization. In an Islamic perspective, everything must be done in a neat, correct, orderly and orderly manner.